Virtual lower limb stroke rehabilitation to assess post stroke patients - Syadiah Nor, Wan Shamsuddin; Jian, Lee Wei (2019)
. Stroke is a disease that causes disability in adults due to the abrupt interruption of constant blood flow to the brain. Most people encounter difficulties with movement after a stroke, which prevents them from moving around. However, patients often show a lessened endurance and motivation in participating in these boring exercises. This may lead to an early termination of stroke rehabilitation, which can cause permanent disability in life. The application of virtual reality in stroke rehabilitation provides an immersive environment to increase the engagement of patients in rehabilitation exercises. In this study, a prototype named virtual lower limb stroke rehabilitation (VRLite) was developed and tested with post stroke patients on the accuracy of measurements and its usability and acceptance. The measurements of knee angles using Kinect and goniometer were compared using Bland-Altman plot to assess the system validity. The upper and lower LoA were 7.2° and −7.5° respectively. The result shows that 95% of LoA were within the upper and lower limit. The result shows that there is no significant difference between the measurements of knee angles using Kinect and goniometer. Hence, the developed program can be used interchangeably with the conventional rehabilitation.